2020
DOI: 10.1111/ijfs.14852
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibition of Fusarium graminearum and deoxynivalenol detoxification by lactic acid bacteria and their application in sourdough bread

Abstract: Eight lactic acid bacteria (LAB) strains were screened for their ability to inhibit Fusarium graminearum (F. graminearum) growth and remove deoxynivalenol (DON). Furthermore, the selected LAB strains were applied as starter cultures to evaluate their performance during the breadmaking process. Lactobacillus plantarum (L. plantarum) AR524 exhibited strong inhibitory activity against F. graminearum growth in a pH-dependent manner and removed up to 40.9% of DON, mainly through cell wall binding. Compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Recently, LAB have been investigated as preservative agents to control spoilage agents, which are commonly present in cereals and cereal-derived food products, causing quality and sensory deterioration [6]. Although chemical preservatives are still widely used, the food industry is forced to provide innovative products by reconsidering the microbial fermentation process and bio-compounds as an alternative to satisfy the consumer's demands for healthy and clean-label food [7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, LAB have been investigated as preservative agents to control spoilage agents, which are commonly present in cereals and cereal-derived food products, causing quality and sensory deterioration [6]. Although chemical preservatives are still widely used, the food industry is forced to provide innovative products by reconsidering the microbial fermentation process and bio-compounds as an alternative to satisfy the consumer's demands for healthy and clean-label food [7].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that 58% of the total LA is dissociated at pH 4, which is estimated to increase to 86% at pH 4.6 at 30 • C [34,35]. Some evidence has shown that the dissociation of organic acids limits their penetration into the fungal cells, thereby resulting in their low efficiency in inhibiting fungi [29,36]. In this study, the antifungal effect of Lpb.…”
Section: Discussionmentioning
confidence: 71%
“…When the pH is lower than the pKa of the organic acids, the non-dissociated form predominates and can cross the fungal cell membrane by passive diffusion, leading to the accumulation of organic acids in the cytoplasm and the inhibition of fungal growth. However, high pH causes organic acids to be dissociated, and these dissociated organic acids cannot readily penetrate through the cell membrane, decreasing the antifungal effect of organic acids [28,29]. Furthermore, the antifungal effect of some active compounds in the CFS is pH-dependent, and pH neutralization reduces their antifungal activity [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the growth of LAB lowers the pH of the media, which causes difficulty for other competing microorganisms to grow (Harada et al, 2017). In this study, the inhibition of C. versatilis propagation was probably due to a significant amount of lactic acid production and accumulation, which might have damaged the cytoplasm of the yeast cell, as well as disrupted the proton motor forces (Cao et al, 2021). Also, the production of growth-inhibitory compounds and competition of essential nutrients by L. lactis might also cause the antagonistic interactions (Devanthi et al, 2018b).…”
Section: Growth Of L Lactis and C Versatilismentioning
confidence: 74%
“…In this study, the inhibition of C . versatilis propagation was probably due to a significant amount of lactic acid production and accumulation, which might have damaged the cytoplasm of the yeast cell, as well as disrupted the proton motor forces (Cao et al ., 2021). Also, the production of growth‐inhibitory compounds and competition of essential nutrients by L .…”
Section: Resultsmentioning
confidence: 99%